Pengaruh Self Confidence Terhadap Hasil Belajar Matematika Siswa Kelas VIII SMP - Valentina Isyana, Besty; Baidowi; Novitasari, Dwi; Sridana, Nyoman (FKIP Universitas Mataram, 2024)
This study aims to analyze the self-cofidence and mathematics learning outcomes of students and to show the significant influence of self-cofidence on the mathematics learning outcomes of grade students in one of the junior high schools in the city of Mataram. The subjects in this study were 27 students from grade C who were selected by cluster random sampling technique. Data collection techniques in this research are self-confidence and mathematics learning outcomes tests. Data collection techniques in this research were self-confidence questionnaires and mathematics learning outcomes tests. The results of self-confidence data analysis and mathematics learning outcomes tests show that: (1) self-confidence indicators with good categories, namely optimism, responsibility, being objective, rational or realistic, improving abilities and skills, successes and failures obtained, as well as acceptance and appreciation in the classroom, while indicators of belief in one's own abilities are in the fairly good category. As for the mathematics learning results, it shows that students are more capable in the aspect of knowledge than skills, for mathematical problem solving, students have shown their ability at the stage of understanding problems and preparing problem solving plans quite well, while the ability of students at the stage of implementing the plan and re-examining problem solving is still low; (2) There is a significant influence of self-confidence on the mathematics learning outcomes of grade junior high school students, with a contribution of 33.9%